INOVASI KEMASAN BERKELANJUTAN UKM PASAR KEMIS: INTEGRASI TEKNOLOGI CUTTING STIKER DAN REDESAIN KEMASAN DALAM MENGHADAPI TANTANGAN MODERN MARKET - Novi Purnama Sari; Wiwi Prastiwinarti; Ade Isna; Devyta Maharani; Fahri Fadhillah; Iqbal Yamin; Lytta Yennia Putri; Raditya Naufal; Rizwan (Universitas Negeri Surabaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing more than 60.5% to Gross Domestic Product (GDP) in 2022. However, MSMEs face significant challenges in the digital era, especially in adapting technology to achieve sustainability and efficiency. The use of technology in the production and packaging process is key for MSMEs to expand market access, reduce production costs, and offer competitive prices. In order to improve the competitiveness of MSMEs in Pasar Kemis District, Tangerang Regency, MSMEs Anugerah Bosstea Mandiri, BAJARA Jus, and Dimsum Dapur Mama Nove participated in a community service program aimed at improving understanding of effective packaging strategies. This program involves the use of automatic sticker cutting tools and vacuum sealers, designed by the Packaging Printing Industry Technology (TICK) Study Program, to address label design and product durability issues. This activity also includes comprehensive training on food preservation, packaging regulations, and the use of food additives, with a focus on realizing sustainable and competitive MSMEs in the modern market. The results are expected to improve the quality and competitiveness of MSME products in an increasingly competitive market.